2022
DOI: 10.3389/fonc.2022.1032850
|View full text |Cite
|
Sign up to set email alerts
|

WFDC21P promotes triple-negative breast cancer proliferation and migration through WFDC21P/miR-628/SMAD3 axis

Abstract: Long non-coding RNAs (lncRNAs) modulate cell proliferation, cycle, and apoptosis. However, the role of lncRNA-WFDC21P in the tumorigenesis of triple-negative breast cancer (TNBC) remains unclear. Results of this study demonstrated that WFDC21P levels significantly increased in TNBC, which was associated with the poor survival of patients. WFDC21P overexpression significantly promoted TNBC cell proliferation and metastasis. WFDC21P interacted with miR-628-5p, which further suppressed cell proliferation and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…As shown in previous studies, WFDC21P attenuates hepatocarcinogenesis via modulating glycolysis [ 36 ]. On the opposite side, studies showed that WFDC21P promoted lung [ 37 ], breast [ 38 ], and colorectal tumor [ 39 ] malignant behaviors. In this study, WFDC21P was upregulated in both gastric cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in previous studies, WFDC21P attenuates hepatocarcinogenesis via modulating glycolysis [ 36 ]. On the opposite side, studies showed that WFDC21P promoted lung [ 37 ], breast [ 38 ], and colorectal tumor [ 39 ] malignant behaviors. In this study, WFDC21P was upregulated in both gastric cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that non-coding RNAs (ncRNAs) interacted with miRNAs or proteins to act as molecular sponge [ 40 , 41 ]. In previous studies, WFDC21P was reported to bind with miR-4293 [ 37 ] and miR-628 [ 38 ] to regulate lung and breast cancer progression respectively. On the other aspect, studies showed that WFDC21P was activated by transcription factor Nur77 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower chamber contains 600 μL of 30% FBS medium. The subsequent processing is according to the previous reports 37 , 38 .…”
Section: Methodsmentioning
confidence: 99%
“…WFDC21P interacts with miR-628-5p, and significantly accelerates proliferation and migration of TNBC cells via the Smad3 signaling pathway. 70 The METTL3-mediated m6A modification positively regulates LINC00520, which then acts as a sponge for miR-577, leading to elevated POSTN levels and activation of the downstream ILK/AKT/ mTOR pathway, promoting BC cell proliferation, migration, and EMT. 71 Furthermore, METTL14-mediated m6A modification improves the m6A level of the oncogenic molecule lncRNA AC084125.2 in MDA-MB-231 cells and down-regulates its expression, facilitating BC cell migration and invasion.…”
Section: Regulation Of Lncrnas By M6amentioning
confidence: 99%
“…In TNBC cells (SUM159 and BT549), METTL3 upregulates lncRNA‐WFDC21P expression and m6A level through m6A modification. WFDC21P interacts with miR‐628‐5p, and significantly accelerates proliferation and migration of TNBC cells via the Smad3 signaling pathway 70 . The METTL3‐mediated m6A modification positively regulates LINC00520, which then acts as a sponge for miR‐577, leading to elevated POSTN levels and activation of the downstream ILK/AKT/mTOR pathway, promoting BC cell proliferation, migration, and EMT 71 .…”
Section: Regulation Of Ncrnas By M6a In Bcmentioning
confidence: 99%